Application of tuned-mass dampers in vibration reduction design for fortifications by three dimentional structural model - Nguyễn Thành, Đồng (Journal of Military Science and Technology, 2022)
Fortification structures are generally subjected to intense dynamic loads, causing strong vibrations. The fortification structure design focuses mainly to ensure durable conditions without mentioning anti-vibration solutions. The Tuned Mass Damper is known as a highly effective solution in reducing vibrations for structures. The paper study the application of TMD devices in the design of shock absorbers for fortifications subjected to dynamic loads. The analytical solutions are established on a simplified single-degree-of-freedom system. The 3D structural models of a specific fortification subjected to dynamic loads were analyzed using SAP2000 software. The efficiency of TMD was investigated by comparing the dynamic response of the structure using TMD and without TMD. The results show that the TMD device provides high efficiency in reducing the amplitude and frequency of the structural vibration.